ANTHONY GIDDENS'S STRUCTURATION THEORY AND RELEVANCE WITH SOCIOLOGY OF KNOWLEDGE - Rifqi Khairul Anam (PT Innovative Academic Journals, 2025)
Anthony Giddens's structuration theory serves as a pivotal framework in contemporary social theory, illuminating the intricate relationship between human agency and societal structures. Central to this theory is the